Our Higher Calling : Rebuilding the Partnership between America and Its Colleges and Universities - Thorp, H. Holden, 1964-; Goldstein, Buck (Book collections on Project MUSE., 2018)
Americans from all walks of life are losing confidence in American higher education and their numbers are increasing at an alarming rate. Amidst this decline in public support, many American colleges and universities now must confront an unstainable business model. Holden Thorp and Buck Goldstein address these problems head on, articulating the real challenges facing higher education and describing in pragmatic terms what can and cannot change - and what should and should not change.